Tuberculous Spondylitis Following Kyphoplasty: A Case Report and Review of the Literature. Issue 11 (March 2016) - Ge, Chao-Yuan; He, Li-Ming; Zheng, Yong-Hong; Liu, Tuan-Jiang; Guo, Hua; He, Bao-Rong; Qian, Li-Xiong; Zhao, Yuan-Tin; Yang, Jun-Song; Hao, Ding-Jun
Abstract : Abstract: Tuberculous spondylitis of the augmented vertebral column following percutaneous vertebroplasty or kyphoplasty has rarely been described. We report an unusual case of tuberculous spondylitis diagnosed after percutaneous kyphoplasty (PKP). A 61-year-old woman presented to our institution complaining of back pain following a fall 7 days before. Radiologic studies revealed an acute osteoporotic compression L1 fracture. The patient denied history of pulmonary tuberculosis (TB) and there were no signs of infection. The patient was discharged from hospital 4 days after undergoing L1 PKP with a dramatic improvement in her back pain. Two years later, the patient was readmitted with a 1 year history of recurrent back pain. Imaging examinations demonstrated long segmental bony destruction involving L1 vertebra with massive paravertebral abscess formation. The tentative diagnosis of tuberculous spondylitis was made, after a serum T-SPOT. The TB test was found to be positive. Anterior debridement, L1 corpectomy, decompression, and autologous rib graft interposition, and posterior T8-L4 instrumentation were performed. The histologic examination of the resected tissue results confirmed the diagnosis of spinal TB. Anti-TB medications were administered for 12 months and the patient recovered without sequelae. Spinal TB and osteoporotic vertebral compression fractures are similar clinically and radiologically. Spinal surgeons should consider this disease entity to avoid misdiagnosis or complications. Early surgical intervention and anti-TB treatment should be instituted as soon as the diagnosis of spinal TB after vertebral augmentation is made.